The Use of “Literary Fiction” to Promote Mentalizing Ability - Pino, Maria Chiara; Mazza, Monica (PLOS ONE, 2016)
Empathy is a multidimensional process that incorporates both mentalizing and emotional sharing dimensions. Empathic competencies are important for creating interpersonal relationships with other people and developing adequate social behaviour. The lack of these social components also leads to isolation and exclusion in healthy populations. However, few studies have investigated how to improve these social skills. In a recent study, Kidd and Castano (2013) found that reading literary fiction increases mentalizing ability and may change how people think about other people’s emotions and mental states. The aim of our study was to evaluate the effects of reading literary fiction, compared to nonfiction and science fiction, on empathic abilities. Compared to previous studies, we used a larger variety of empathy measures and utilized a pre and post-test design. In all, 214 healthy participants were randomly assigned to read a book representative of one of three literary genres (literary fiction, nonfiction, science fiction). Participants were assessed before and after the reading phase using mentalizing and emotional sharing tests, according to Zaki and Ochsner’ s (2012) model. Comparisons of sociodemographic, mentalizing, and emotional sharing variables across conditions were conducted using ANOVA. Our results showed that after the reading phase, the literary fiction group showed improvement in mentalizing abilities, but there was no discernible effect on emotional sharing abilities. Our study showed that the reading processes can promote mentalizing abilities. These results may set important goals for future low-cost rehabilitation protocols for several disorders in which the mentalizing deficit is considered central to the disease, such as Autism Spectrum Disorders and Schizophrenia.